2013
DOI: 10.1113/jphysiol.2013.263657
|View full text |Cite
|
Sign up to set email alerts
|

Cellular properties and chemosensory responses of the human carotid body

Abstract: Key points• The carotid body (CB) is a key chemoreceptor organ that mediates the hyperventilatory response to hypoxia, and contributes to the process of acclimatisation to chronic hypoxaemia.• Knowledge of CB physiology at the cellular and molecular levels has advanced considerably in recent times thanks to studies on lower mammals; however, information on humans is practically absent. Here we describe the properties of human CB cells in slice preparations or after enzymatic dispersion.• Besides glomus (type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 61 publications
4
62
1
Order By: Relevance
“…Nonetheless, other authors have failed to fi nd any responsiveness of explanted whole CB preparations to low glucose (Bin-Jaliah et al 2004 ;Conde et al 2007 ) or any signifi cant changes in cytosolic [Ca 2+ ] in dispersed glomus cells in response to rapid glucose removal (Gallego-Martin et al 2012 ). In contrast to these last observations, we have found that, as in the rat (Garcia-Fernandez et al 2007 ), human glomus cells can also depolarize and release transmitters in response to a decrease in the extracellular glucose concentration (Ortega-Saenz et al 2013 ). Under normoxic conditions (PO 2 ~ 150 mmHg), removal of extracellular glucose produced membrane depolarization, an increase in cytosolic [Ca 2+ ] and a secretory response in human glomus cells similar to that obtained in rodent cells subjected to the same experimental protocol (Fig.…”
Section: Cellular Responses To Hypoglycemiacontrasting
confidence: 73%
See 3 more Smart Citations
“…Nonetheless, other authors have failed to fi nd any responsiveness of explanted whole CB preparations to low glucose (Bin-Jaliah et al 2004 ;Conde et al 2007 ) or any signifi cant changes in cytosolic [Ca 2+ ] in dispersed glomus cells in response to rapid glucose removal (Gallego-Martin et al 2012 ). In contrast to these last observations, we have found that, as in the rat (Garcia-Fernandez et al 2007 ), human glomus cells can also depolarize and release transmitters in response to a decrease in the extracellular glucose concentration (Ortega-Saenz et al 2013 ). Under normoxic conditions (PO 2 ~ 150 mmHg), removal of extracellular glucose produced membrane depolarization, an increase in cytosolic [Ca 2+ ] and a secretory response in human glomus cells similar to that obtained in rodent cells subjected to the same experimental protocol (Fig.…”
Section: Cellular Responses To Hypoglycemiacontrasting
confidence: 73%
“…The estimated volume of the adult human CB in our cohort is 20.7 ± 3.8 mm 3 (n = 16 carotid bodies; 11 donors), a value within the range reported by other studies (Heath et al 1970 ;Shamblin et al 1971 ;Arias-Stella and Valcarcel 1976 ). However, large differences in sizes are observed among the different individuals or even between the right and left CBs of the same subject (Ortega-Saenz et al 2013 ). Although there is a trend for CBs from males to be larger than those of females, no statistically signifi cant differences was found associated to sex (Fig.…”
Section: Structure and Gdnf Content Of The Human Cbsupporting
confidence: 62%
See 2 more Smart Citations
“…Chronic activation of the sympathetic nervous system may be a pathway toward the development of metabolic syndrome (Brotman et al, 2002). Alternatively, new findings suggest that hypoglycemia stimulates and hyperglycemia inhibits peripheral chemoreceptor responsiveness, and may imply that serum glucose is a driver for sympathetic tone thereby affecting oxygenation through respiratory drive (Ortega-Saenz et al, 2013).…”
Section: Figmentioning
confidence: 99%